Antibiotic susceptibility profile and prevalence of mecA and lukS-PV/lukF-PV genes in Staphylococcus aureus isolated from nasal and pharyngeal sources of medical students in Ecuador - Bastidas, Carlos A (Infect Drug Resist, 2019)
BACKGROUND: Staphylococcus aureus is a common nasal colonizer in 20–30% of the general population. When mucosal and cutaneous barriers are disrupted, S. aureus can cause severe infections. While MRSA nasal carriers have an increased risk of infections when compared to non-carriers, prolonged exposure to the hospital environment may cause an increase in carriage of MRSA. MATERIALS AND METHODS: A survey questionnaire was filled for analyzing risk factors of colonization. Swab isolates were identified as S. aureus by traditional microbiological assays. Antibiotic susceptibility profiles were performed following the CLSI standard guidelines. Multiplex PCR was conducted to determine the presence of genes mecA and lukS-PV/lukF-PV. Chi-squared, univariate, and multivariate logistic regressions were applied to find statistically significant associations between risk factors and the presence of S. aureus and MRSA. RESULTS: One hundred and eighty-six isolates were identified as S. aureus. The strains showed high resistance to penicillin, oxacillin, azithromycin, erythromycin, clindamycin (inducible), and tetracycline. The overall prevalence of MRSA in medical students was 45.9% [40.4–51.6] 95% CI. PCR showed a prevalence of mecA gene in MRSA isolates of 6.1% while lukS-PV/lukF-PV gene was present in 3.2% [1.2–6.9] 95% CI of the S. aureus samples. The risk factors frequency of antibiotic intake and repeated visits to hospitals demonstrated statistical significance. CONCLUSION: S. aureus and MRSA isolates have a high prevalence of colonization, and antibiotic resistance in the population studied. MRSA resistance was not related to the presence of the mecA gene. The prevalence of PVL genes was low, but it could represent a risk because they are circulating in the community.